Trauma Talk - Siri Husvedt (Sillages Critiques)
At the crossroads between theoretical reflections, autobiographical and fictional writings by the author, memories and dreams, not to mention essays by philosophers, psychoanalysts and neuroscientists, this extremely personal and creative paper aims at defining the specificity of trauma narratives – such an endeavor being conceived as essentially paradoxical. Notably, it delves into the representation and the conceptions of memory and time and their relations, as well as their inscription in the body.